A roadmap for the conservation of freshwater mussels in Europe - Sousa, Ronaldo; Zając, Tadeusz; Halabowski, Dariusz; Aksenova, Olga V; Bespalaya, Yulia V; Carvalho, Francisco; Castro, Paulo; Douda, Karel; da Silva, Janine P; Ferreira-Rodríguez, Noé; Geist, Juergen; Gumpinger, Clemens; et al. (Conservation biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long-term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short- and long-term conservation of freshwater mussels across Europe.
Keywords: Biodiversity; freshwater ecosystems; governance; Ecosystem; mlži; education; Europe; biodiverzita; Bivalvia; sladká voda; Fresh Water; ecosystem services; Evropa; Conservation of Natural Resources; Animals; lidé; zachování přírodních zdrojů; Humans; zvířata; ekosystém; Unionida